TELEGRAM BOT USAGE AS AN INSTRUCTIONAL DESIGN METHOD - Ts. Nur Elimtiaz Abidin; Noor Haty Nor Azam; Mohd Azmil Mohd Yusof (International Journal of Accounting, Finance and Business, 2022)
In Malaysia, educational institutions have shifted to online learning in response to Malaysia’s Ministry of Higher Education's current requirement. In response to this requirement, there is a sudden surge among academicians in conducting their delivery methods for online education purposes; for instance, learning management systems, websites, social media platforms, and collaborative applications such as Microsoft Teams and Google Classroom. However, the current method being used is still insufficient as it was hampered by various critical disadvantages which discounted its objective effectiveness. Academicians must not disregard students with limited internet quotas and low-speed internet connections. To fill the gap, this paper aims to discuss Telegram Bot usage and its advantages as an instructional design method. Besides, a survey had been conducted on a group of students before implementing Telegram Bot in the whole class. As a result of the students’ feedback, Telegram Bot can be used as one of the educational tools which support the teaching and learning process.